Particulated Articular Cartilage: CAIS and DeNovo NT - Farr, Jack; Cole, Brian J.; Sherman, Seth; Karas, Vasili (The Journal of Knee Surgery, 2012)
Cartilage Autograft Implantation System (CAIS; DePuy/Mitek, Raynham, MA) and DeNovo Natural Tissue (NT; ISTO, St. Louis, MO) are novel treatment options for focal articular cartilage defects in the knee. These methods involve the implantation of particulated articular cartilage from either autograft or juvenile allograft donor, respectively. In the laboratory and in animal models, both CAIS and DeNovo NT have demonstrated the ability of the transplanted cartilage cells to “escape” from the extracellular matrix, migrate, multiply, and form a new hyaline-like cartilage tissue matrix that integrates with the surrounding host tissue. In clinical practice, the technique for both CAIS and DeNovo NT is straightforward, requiring only a single surgery to affect cartilage repair. Clinical experience is limited, with short-term studies demonstrating both procedures to be safe, feasible, and effective, with improvements in subjective patient scores, and with magnetic resonance imaging evidence of good defect fill. While these treatment options appear promising, prospective randomized controlled studies are necessary to refine the indications and contraindications for both CAIS and DeNovo NT.
Keywords: particulated cartilage allograft; Cartilage Autograft Implantation System; DeNovo Natural Tissue